2019
DOI: 10.1038/s41598-019-40989-6
|View full text |Cite
|
Sign up to set email alerts
|

Night workers have lower levels of antioxidant defenses and higher levels of oxidative stress damage when compared to day workers

Abstract: The effects of circadian misalignment and work shift on oxidative stress profile of shift workers have not been explored in the literature. The present study aimed to evaluate the role of shift work (day and night) and social jetlag - a measure of circadian misalignment - with oxidative stress markers. A cross-sectional study was performed with 79 men (21–65 years old, 27.56 ± 4.0 kg/m2) who worked the night shift (n = 37) or daytime (n = 42). The analyzed variables included anthropometric measures and determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 75 publications
1
47
0
Order By: Relevance
“…In contrast, night shift work may lead to impaired pineal function and inhibit melatonin production ( James et al, 2017 ). Teixeira et al reported that night shift workers have a higher level of oxidative stress damage and a lower level of antioxidant defenses ( Teixeira et al, 2019 ). Women who rotate night shift work have an increased risk of early menopause and ovarian failure ( Stock et al, 2019 ).…”
Section: Natural Antioxidant-based Interventions To Reduce Oxidative mentioning
confidence: 99%
“…In contrast, night shift work may lead to impaired pineal function and inhibit melatonin production ( James et al, 2017 ). Teixeira et al reported that night shift workers have a higher level of oxidative stress damage and a lower level of antioxidant defenses ( Teixeira et al, 2019 ). Women who rotate night shift work have an increased risk of early menopause and ovarian failure ( Stock et al, 2019 ).…”
Section: Natural Antioxidant-based Interventions To Reduce Oxidative mentioning
confidence: 99%
“…Suppression of the immune system resulting in pathogenic microorganisms in blood and sepsis was recorded in sleep-deprived rats [63]. Long-term sleep deprivation leads to oxidative stress, reducing the activity of antioxidant enzymes [64,65]. Consequently, long-term sleep deprivation and/or chronic stress leads to the deterioration of immune functions through the disturbance of barrier mechanisms by suppressing the phagocytosis, reducing proliferation and activity of some leukocytes, in particular CD4 þ T cells, while increasing T-suppressors as well as elevating oxidative stress and pro-inflammatory background.…”
Section: Melatonin Can Reduce Immunosuppression Induced By Chronic Stmentioning
confidence: 99%
“…Indeed, melatonin play its role as antioxidant in human cells only at its pharmacological concentrations (Reiter et al, 1994). The reduction in the activity of antioxidant enzymes due to the long-term sleep deprivation leads to the development of oxidative stress ( Ramanathan et al, 2002 ; Teixeira et al, 2019 ) and consequently deterioration of immune functions. Because of significant impairment in melatonin production in people with chronic insomnia, taking melatonin may restore the normal sleep pattern and decrease anxiety during COVID-19 crisis (Shneider et al).…”
Section: Potential Of Supplements For Covid-19mentioning
confidence: 99%